Towards an understanding of nursing as a response to human vulnerability - Sellman, Derek (Nursing philosophy, 2005)
It is not unusual for the adjective ‘vulnerable’ to be applied to those in receipt of nursing practice without making clear what it is that persons thus described are actually vulnerable to. In this paper I argue that the way nursing has adopted the idea of vulnerability tends to imply that some people are in some way invulnerable. This is conceptually unsustainable and renders the idea of the vulnerable patient (almost) meaningless. The paper explores the meaning of vulnerability both in general terms and in the context of nursing practice. It is argued that to be in receipt of nursing is to become, to a greater or lesser extent, more-than-ordinary vulnerable. Thus all patients are more-than-ordinarily vulnerable and this restricts their potential to flourish. Nurses are well placed to contribute to the flourishing of more-than-ordinarily vulnerable persons and my substantive claim is that this ‘protective’ function is indeed a legitimate and fundamental part of the role of nurses.